EKSPLORASI KEPEMIMPINAN KEPALA SEKOLAH BERBASIS SERVANT LEADERSHIP DALAM MEMBANGUN BUDAYA POSITIF DI LINGKUNGAN SEKOLAH - Warman, Warman; Kadori, Kadori; Lorensius, Lorensius (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study focuses on the leadership of school principals at Tabang Elementary School. Employing a qualitative case study approach, data were gathered from teachers through interviews, observations, and documentation. The research findings highlight three main aspects of servant leadership: humanity, openness, and courage in facing challenges. School principals are identified not only as administrators but also as facilitators and leaders who empower the school community. These results can serve as inspiration for other schools to adopt servant leadership principles, enhance educational quality, and prepare students for the future.